Automatic generation of GUIs that optimise energy consumption in Android applications based on GEMMA and colour psychology (2019)
The growing use of mobile devices in everyday life has forced developers to create mobile applications that allow users to do different tasks. Developers should create applications that should be easy to use and should have simple and beautiful inter-faces. But the real challenge of these developers is to ensure that these applications are usable, optimising the use of limited resources of the devices. The use of resources includes energy consumption and memory. Then it becomes very important to generate savings in the consumption of these elements. Specifically for energy consumption, it is possible to generate savings for devices with OLED or AMOLED displays, where the energy consumption depends on the colours shown. The GEMMA tool allows the generation of GUIs that optimise energy consumption, based on optimisation using genetic algorithms. Although this tool generates GUIs and its validations have been satisfactory, it does not include aspects of the psychology of color. Therefore, in this work different techniques for the inclusion of the psychology of color in GEMMA are explored, guaranteeing colours that decrease the energy consumption in OLED and AMOLED screens.